Pemetaan Kasus Stunting di Kabupaten Lamongan Tahun 2023 - Ananda Azmi Mufida; Mohamad Anis Fahmi (Ficco Public Health Journal, 2024)
Background: Stunting is a condition in toddlers who experience growth failure due to chronic malnutrition that causes children to be shorter than their group. The results of the Indonesia Nutrition Status Survey (SSGI) in 2022 show that the prevalence of stunting in Lamongan Regency is 27.5%. and is still above the WHO standard of ≤20%. The purpose of this study is to find out if there is a spatial autocorrelation of stunting incidence in Lamongan Regency in 2023. Methods: The methods used are Moran Index, Moran's Scatterplot, Local Indicator of Spatial Association (LISA). Results: The value of the Moran Index of stunting incidence was 0.1851, indicating a positive spatial autocorrelation or forming a grouping pattern. Population Density with Stunting Incidence of -0.1966 indicates a negative spatial autocorrelation or random pattern of spreading. The availability of clean water with a stunting incidence is -0.3497 which indicates a negative spatial autocorrelation or a random spreading pattern. Conclusions: There is a positive Spatial Autocorrelation or forming a clustered pattern in stunting events in Lamongan Regency in 2023, There is a negative spatial autocorrelation of random distribution patterns between population density and stunting events in Lamongan Regency in 2023, There is a negative spatial autocorrelation of random distribution patterns between the availability of clean water and stunting events in Lamongan Regency in 2023.